Ameliorating the antitumor activity of gemcitabine against breast tumor using αvβ3 integrin-targeting lipid nanoparticles. (3rd August 2022) - Tunki, Lakshmi; Ganthala, Parimala Devi; Pooja, Deep; Andugulapati, Sai Balaji; Kulhari, Hitesh; Sistla, Ramakrishna; Bhargava, Suresh Kumar
Abstract: Objective: The main objective is to formulate solid lipid nanoparticles conjugated with cyclic RGDfk peptide encapsulated with gemcitabine hydrochloride drug for targeting breast cancer. Significance: The hydrophilic nature of gemcitabine hampers passive transport by cell membrane permeation that may lead to drug resistance as it has to enter the cells via nucleoside transporters. The art of encapsulating the drug in a nanovesicle and then anchoring it with a targeting ligand is one of the present areas of research in cancer chemotherapy. Methods: In this study, solid lipid nanoparticles were prepared by double emulsification and solvent evaporation method. Cyclic RGDfk and gemcitabine hydrochloride were used as targeting ligands and chemotherapeutic drugs, respectively, for targeting breast cancer. The prepared nanoparticles were evaluated for in vitro and in vivo performance to showcase the targeting efficiency and therapeutic benefits of the gemcitabine-loaded ligand conjugated nanoparticles. Results: When compared with gemcitabine (GEM) and GEM loaded nanoparticles (GSLN), the ligand conjugated GEM nanoparticles (cGSLN) showed superior cytotoxicity, apoptosis, and inhibition of 3D multicellular spheroids in human breast cancer cells (MDA MB 231). The in vivo tumor regression studies in orthotopic breast cancer induced Balb/C mice showed that cGSLN displayed superior tumor suppression and also the targeting potential of the cGSLN toward induced breast cancer. Conclusion: Prepared nanoformulations showed enhanced anticancer activity in both 2D and 3D cell culture models along with antitumor efficacy in orthotopic breast cancer mouse models. Graphical Abstract: UF0001